2021
DOI: 10.1136/bmjresp-2021-000960
|View full text |Cite
|
Sign up to set email alerts
|

Stability in eosinophil categorisation during subsequent severe exacerbations of COPD

Abstract: BackgroundThe blood eosinophil count has been shown to be a promising biomarker for establishing personalised treatment strategies to reduce corticosteroid use, either inhaled or systemic, in chronic obstructive pulmonary disease (COPD). Eosinophil levels seem relatively stable over time in stable state, but little is known whether this is also true in subsequent severe acute exacerbations of COPD (AECOPD).Aims and objectivesTo determine the stability in eosinophil categorisation between two subsequent severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For this interesting phenomenon, the specific mechanism is still unclear and controversial. It is speculated that although eosinophil is related to exacerbations, patients with high eosinophil are sensitive to inhaled corticosteroid (ICS) ( 43 ), thus have a better response to therapy resulting in quicker recovery ( 13 ). Secondly, it was found that lower eosinophilic COPD patients had higher neutrophil counts.…”
Section: Discussionmentioning
confidence: 99%
“…For this interesting phenomenon, the specific mechanism is still unclear and controversial. It is speculated that although eosinophil is related to exacerbations, patients with high eosinophil are sensitive to inhaled corticosteroid (ICS) ( 43 ), thus have a better response to therapy resulting in quicker recovery ( 13 ). Secondly, it was found that lower eosinophilic COPD patients had higher neutrophil counts.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Citgez et al analyzed the EOS of patients hospitalized for AECOPD on two occasions before and after, based on cut-off values of 200/ul, 300/ul, 2%, and 3%, respectively, and showed overall stability of EOS of 70–85%. 12 We chose a cut-off value of 150 cells/ul because studies have shown that this value is more useful for assessing the stability of blood EOS and also for differentiating patients prone to deterioration. 13 , 14 Our results showed that the stability of blood EOS was 77.2%, suggesting that the stability of blood EOS in patients hospitalized with AECOPD was relatively stable over 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Even if asthma control in patients is stable, the blood eosinophil counts still fluctuate substantially ( 16 ). In contrast, while blood eosinophils are stable over time in stable COPD, the counts are unstable in severe acute exacerbation of COPD (AECOPD) because of the variety of causes of AECOPD ( 17 ).…”
Section: .Relationship Between Blood Eosinophilia and Clinical Outcom...mentioning
confidence: 99%